E-Commerce Based Website With Method Economic Order Quantity (EOQ): E-Commerce Based Website With Method Economic Order Quantity (EOQ) - Ani Rahmawati; Iskandar Fitri; Nur Hayati (Jurnal Mantik, 2020)
Based on the observations it can be seen that problems in Tumblertees sales transaction process is still done manually which led to the possibility of human error that would result in misinformation and also experience problems with over-stock so that the proper stock management is needed in order to avoid waste of product purchase. This study build an e-commerce based website by using the waterfall model as the development of the system and apply the method Economic Order Quantity (EOQ) to facilitate the ordering process, the sale and purchase of products on Tumblertees. The test results showed that the use of the method of Economic Order Quantity (EOQ) is able to reduce costs to support the increase in sales turnover.